2005
DOI: 10.1080/07853890500317414
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tumor necrosis factor‐alpha and ammonia in patients with hepatic encephalopathy due to chronic liver failure

Abstract: The results of this study demonstrate a significant relationship between TNF and ammonia in patients with chronic liver failure and HE, and so strengthen the suggestion that TNF could be strongly involved in the pathogenesis of HE in these patients. Hence, we suggest a new theory in the pathogenesis of HE, the "TNF theory".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
68
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 41 publications
10
68
2
Order By: Relevance
“…It has recently been suggested that inflammatory mediators might play a crucial role in the pathogenesis of this syndrome (27,42,51). Serum levels of inflammatory cytokines have been shown to correlate with the severity of encephalopathy in patients with cirrhosis (43,44). Both the presence of hepatic encephalopathy and the reduction in HRV have negative prognostic value in this patient population (7,17).…”
mentioning
confidence: 99%
“…It has recently been suggested that inflammatory mediators might play a crucial role in the pathogenesis of this syndrome (27,42,51). Serum levels of inflammatory cytokines have been shown to correlate with the severity of encephalopathy in patients with cirrhosis (43,44). Both the presence of hepatic encephalopathy and the reduction in HRV have negative prognostic value in this patient population (7,17).…”
mentioning
confidence: 99%
“…[51][52][53] The production of TNF-␣, a central player in inflammatory reactions, has been shown to be markedly elevated in cirrhosis. 51,54,55 TNF-␣ substantially reduces the expression of 11␤-HSD2, a contention supported by several lines of evidence. First, Takahashi et al reported a decreased 11␤-HSD2 expression in the mineralocorticoid responsive colonic mucosa of patients with inflammatory bowel disease.…”
Section: Biology Of 11␤-hsd2mentioning
confidence: 54%
“…The "TNF theory" of HA/HE pathogenesis [8] emphasizes significant roles of TNF-α and other cytokines in HE up to the extent that these cytokines could be used as markers for encephalopathy grading [4,[9][10][11][12][13]. Obviously, TNF-α could be considered a suitable target for therapeutic intervention, however, with limited information on its responsiveness towards RSV in neuroinflammation and neuroexcitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…During recent past, "TNF theory" (Tumor necrosis factor) of HE pathogenesis could draw much attention due to a close association between the level of TNF-α and ammonia in the brain of CLF patients with HE [8]. Later studies have also emphasized significant involvement of TNF-α and other cytokines in HE to the extent that these cytokines could be used as markers for encephalopathy grading [4,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation